HUBUNGAN THINKING STYLE DENGAN RESILIENSI MAHASISWA TINGKAT AKHIR YANG SEDANG MENGERJAKAN SKRIPSI - Silvi Ersa Putri; Evanytha Evanytha; Andi Eka Septilla (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2026)
This study aims to analyze the relationship between thinking styles and resilience among university students working on their undergraduate thesis. The research involved 123 students from semesters 7 to 14 who were actively writing their thesis. A quantitative approach was used, with data analysis conducted through normality, validity, reliability, and correlation tests, assisted by SPSS version 23. The data collected were numerical, illustrating the relationship between thinking styles and resilience. The result showed a significant correlation between the thirteen types of thinking styles and students’ resilience levels. Among these, the four most dominant thinking styles identified were legislative, monarchical, executive, and liberal. These findings suggest that certain thinking styles may influence an individual’s level of resilience, particularly in facing academic challenges during the thesis writing process.